Developing an approach for decision making units integration using multi objective particle swarm optimization - Haeri, Abdorrahman; Rezaie, Kamran; Hatefi, Seyed Morteza (International Journal of Engineering and Technology, 2014)
In recent years, integration between companies, suppliers or organizational departments attracted much attention. Decision making about integration encounters with major concerns. One of these concerns is which units should be integrated and what is the effect of integration on performance measures. In this paper the problem of decision making unit (DMU) integration is considered. It is tried to integrate DMUs so that the considered criteria are satisfied. In this research two criteria are considered that are mean of efficiencies of DMUs and the difference between DMUs that have largest and smallest efficiencies. For this purpose multi objective particle swarm optimization (MOPSO) is applied. A case with 17 DMUs is considered. The results show that integration has increased both considered criteria effectively.Â Additionally this approach can presents different alternatives for decision maker (DM) that enables DM to select the final decision for integration.